Tracing normal lives: between stigma and the will to be Cigano - Magano, O. (2017)
Despite the stereotyped homogenisation of the Ciganos (or Gypsies/Roma) – often perceived as poor and marginalised – many have in fact taken different personal and family life paths. Taking into account a perspective of differentiated socialisation processes, social and family contexts and frames of life experiences, the aim of this paper is to present the main results obtained from a qualitative study where in-depth interviews were conducted with Ciganos integrated in the Portuguese labour market (as employees). Our focus is on the processes of social integration, on the many revelations of social and cultural pluralism, and on Gypsy identity, centring attentions and how such identification often serves to challenge the static and hegemonic conceptions about the cultural traits and representations of this population.